If You Can Bomb It, You Can Litigate It: Climate War, Complicit States, and a World on Fire - Sam Blankenship (Washington University Global Studies Law Review, 2021)
This note explores the legal feasibility of using force to compel countries to action on climate change. It does so to argue that, because using force to compel action on climate change can be justified in the same way as using force to address humanitarian crises such as torture and genocide, the international community is obliged to treat States unwilling to address their contributions to climate change in the same way it treats those violating human rights. It does not advocate for States to use force but for States to recognize the severity of the crisis and act accordingly. This note begins by comparing the efficacy and enforceability of the Paris Agreement to the Rome Statute, international responses to the climate crisis and extreme human rights violations respectively. In comparing the two, this note seeks to highlight the gulf between what the international community can do when so moved, as evinced by the Rome Statute, and the weakness of what it chose to do with the Paris Agreement. This note then surveys traditional use-of-force justifications before finally proposing a model by which limited use of force against nations that refuse to address environmental concerns could be justified using existing theories of jus ad bellum Ultimately, this note calls for strong international legislation requiring individual State action on climate change enforced by an international court similar in scope and jurisdiction to the International Criminal Court.